Cycle of life and analysis of risk of the cyanide in the plant of Orcopampa processes - Del Valle Jurado, Carlos (2006)
The actual existence of cyanide in very significant environmental catastrophes indicates that the cyanide management in the mining operation must be improved. Specifically, disposing right standard in the design and the construction of tailing disposals, water managing, qualification and training labor, fauna protection and the good operation of the systems of warning and emergency, all are areas of high-priority attention. The main reasons of the environmental incidents in the mining operations comes from poor design of management of process waters, the design and the construction and maintenance of tailing disposals, in addition to the frequent accidents in the cyanided pulp transport. In the present investigation, we try to get a cyanide layout of the gold and silver recovery process in the plant of processes of Orcopampa of Buenaventura Company of mines, In order to get it we have sampled with a representative method the pulp and the solutions containing cyanide, to be analyzed in the mining company laboratory.On the basis of the results and the HCN measurements in different places of the metallurgical process we have completed an risk analysis caused by this cyanide consumption with the determination of the present and potential hazards in each stages. After discussing the principles of «good practices» and the philosophy of the «International Code of the Cyanide» and their application to the process used in the mentioned mining unit, we look the profits that are agree with the predicted effort and it is proposed an action plan.